2007
DOI: 10.1177/0022167807310917
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Resistance as Ambivalence: Integrative Strategies for Working With Resistant Ambivalence

Abstract: Resistance to change is a problem that has long evaded easy solutions. In this article, the authors suggest the value of understanding and working with some forms of resistance as ambivalence. They describe resistant ambivalence in the context of an integrative and multivoiced understanding. A person who is ambivalent possesses a voice that moves toward change and a voice that struggles against change. The authors sought therapy methods that were consistent with the multivoiced integrative understanding of amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
0
37
0
4
Order By: Relevance
“…Reflection presumably helps clients clarify both reasons for change and the barriers in the way. Presumably, when clients experience low motivation, this itself would become an object of active interest and reflection, with a resulting movement on the part of the client in a direction of health (Engle & Arkowitz, 2008).…”
Section: Existential and Humanistic Perspectivesmentioning
confidence: 99%
“…Reflection presumably helps clients clarify both reasons for change and the barriers in the way. Presumably, when clients experience low motivation, this itself would become an object of active interest and reflection, with a resulting movement on the part of the client in a direction of health (Engle & Arkowitz, 2008).…”
Section: Existential and Humanistic Perspectivesmentioning
confidence: 99%
“…Indeed, mutual in-feeding needs to be understood in the interpersonal context in which it occurs-the intersubjective field created in all interactions between the therapist and the client (Engle and Arkowitz 2008). According to Engle and Arkowitz (2008), "therapists can facilitate the resolution of resistant ambivalence by creating in-session exercises that increase awareness and integration of disowned aspects of the self" (p.393), in the context of a safe and accepting relationship.…”
Section: Final Remarksmentioning
confidence: 99%
“…Downsizing can disrupt stable routines contributing to reliable performance (Neves & Caetano, 2006) and leave surviving employees feeling vulnerable and unsafe (Stuart, 1996). Change requires employees to move out of their comfort zones (Armenakis, Bernerth, Pitts, & Walker, 2007;Engle & Arkowitz, 2008). This can create a sense of uncertainty (Diamond, 2008;Folger & Skarlicki, 1999;Self & Schraeder, 2009;Stuart, 2006), unpredictability, and uncontrollability (Engle & Arkowitz, 2008) resulting in decreased morale, risk-taking, sense of direction, commitment, and selfesteem along with increased anxiety, disorientation, stress, and insecurity (Stuart, 2006).…”
Section: Downsizing and Organizational Changementioning
confidence: 99%
“…Personal, organizational, and change-specific factors can contribute to employee resistance (Self & Schraeder, 2009) Some have suggested that the term ambivalence be used in place of resistance (Engle & Arkowitz, 2008;Piderit, 2000). Unlike resistance, which involves opposing the change, employees who display ambivalence wrestle with intrapersonal and interpersonal factors that move them simultaneously towards and away from the change (Engle & Arkowitz, 2008;Piderit, 2000).…”
Section: Downsizing and Organizational Changementioning
confidence: 99%
See 1 more Smart Citation